2006
DOI: 10.1016/j.ejheart.2006.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on cardiac performance, exercise capacity and quality of life in patients with heart failure: A meta‐analysis

Abstract: Background: Despite major advances in pharmacological treatment of chronic heart failure (CHF), a number of patients still suffer from dyspnoea, fatigue, diminished exercise capacity and poor quality of life. It is in this context that exercise training is being intensively evaluated for any additional benefit in the treatment of CHF. Aims: To determine the effect of exercise training in patients with CHF on cardiac performance, exercise capacity and health-related quality of life. A meta-analysis was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
179
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(207 citation statements)
references
References 90 publications
22
179
2
4
Order By: Relevance
“…The other studies also demonstrated associatlon of QL evaluated by MLHFQ with the variables of the cardiovasculary test, as well as the distance covered in TC6M 1,23 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The other studies also demonstrated associatlon of QL evaluated by MLHFQ with the variables of the cardiovasculary test, as well as the distance covered in TC6M 1,23 .…”
Section: Discussionmentioning
confidence: 96%
“…The cardiac failure (CF) is one of the main morbimortality causes all over the world, presenting increased incidence levels and prevalence with aging 1,2 . In Brazil, CF is the first cause among the hospitalization cardiovasculary diseases by Sistema Único de Saúde (SUS, Single Health System) in patients over 65 years old, increasing the costs with hospitalization and medications 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…The apoptotic pathway exhibits increased levels with a reduced survival pathway in these situations. Exercise training and eating purple sweet potato yogurt can help to prevent heart failure and apoptosis Kuo et al 2005;Lin et al 2013;van Tol et al 2006;Huang et al 2012). Spontaneously hypertensive rats (SHR) of advanced age exhibit depressed myocardial contractile function and ventricular fibrosis, and as a result, stable compensatory hypertrophy progresses to heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…A superprodução e acúmulo de metabó-litos nos musculosesqueléticos, durante a atividade física, promovem a ativação do ergorreflexo, que leva a estímulos que aumentam de forma exagerada a ação dos sistemas ventilatório, hemodinâmico e sistema nervoso simpático 4 , colaborando para aparecimento da dispneia e intolerância aos esforços. O tratamento exige otimização da terapia farmacológica e não farmacológica, o que inclui programa estruturado de exercício físico 5 que, dentre outros benefícios, proporciona melhora da hiperatividade do ergorreflexo 6 , potência funcional e qualidade de vida 7 , sendo relatado que o exercício de alta intensidade promove benefícios superiores ao exercício moderado contínuo 8,9 .…”
Section: Introductionunclassified